EXPLORING GENDER DIFFERENCES IN MENTAL HEALTH OF HIGHER SECONDARY STUDENTS - Datta, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current study attempted to investigate gender differences in the mental health of higher secondary students. A descriptive survey method was employed with a sample of 540 students (284 female and 256 male), selected through random sampling from 15 General degree Colleges affiliated to the University of Calcutta. The Mental Health Battery (2012) developed by Singh and Sengupta was used to assess students’ mental health. The results revealed a statistically significant difference between male and female students’ mental health scores with male students scoring higher than female students. The findings suggest that male students demonstrated better mental health compared to their female counterparts. The study highlights socio-cultural and familial factors that may contribute to these gender-based differences, emphasizing the need for targeted interventions to promote the mental well-being of female students. The study provides practical implications for educational institutions, policymakers, teachers and parents emphasizing their collaborative role in fostering resilience, reducing stress, and creating supportive environments and prioritizing mental health education and providing equal opportunities for participation to promote adolescent well-being.